La traduction et l’interprétation comme révélateurs des mécanismes de production et de compréhension du discours - Gile, Daniel (Meta)

(untitled) (Les Presses de l'Université de Montréal, 1990)
SummaryTranslation (I/T) constraints reveal that the feeling of "comprehension" is relative and depends on functional requirements, on linguistic familiarity and on a psychological comfort threshold. Translators are aware of the importance of extra-linguistic knowledge and of the intrinsic ambiguity of language. The comprehension of specialized texts by Translators can be modeled using semantic net-like structures.Production is revealed to be a difficult process through errors occurring under I/T constraints. It is also highly vulnerable to linguistic interference. Passive and active lexical mastery of language can be analyzed using a Gravitational Model. Production of informative speech almost invariably involves the introduction of "secondary information" which is not part of the Message.